2022
DOI: 10.3389/fphar.2022.924747
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy and Safety of Ischemic Stroke Therapies: An Umbrella Review

Abstract: Background: Ischemic stroke is a leading cause of morbidity and mortality in neurological diseases. Numerous studies have evaluated the efficacy and safety of ischemic stroke therapies, but clinical data were largely inconsistent. Therefore, it is necessary to summarize and analyze the published clinical research data in the field.Objective: We aimed to perform an umbrella review to evaluate the efficacy and safety of ischemic stroke therapies.Methods: We conducted a search for meta-analyses and systematic rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 64 publications
1
10
0
Order By: Relevance
“…Regarding neurological function, after 6 weeks of treatment, there was a 2.22-point reduction in the NIHSS scores in the MA group compared with the SA group, indicating a clinical improvement in neurological impairment . The effects of acupuncture in enhancing neurological function in patients with stroke have been validated in clinical studies . Moreover, acupuncture is recommended by clinical practices and treatment guidelines for at least 15 poststroke symptoms worldwide .…”
Section: Discussionsupporting
confidence: 86%
“…Regarding neurological function, after 6 weeks of treatment, there was a 2.22-point reduction in the NIHSS scores in the MA group compared with the SA group, indicating a clinical improvement in neurological impairment . The effects of acupuncture in enhancing neurological function in patients with stroke have been validated in clinical studies . Moreover, acupuncture is recommended by clinical practices and treatment guidelines for at least 15 poststroke symptoms worldwide .…”
Section: Discussionsupporting
confidence: 86%
“…Besides, through randomized controlled trials and the meta-analyses, blood-activating TCM combined with western medicine is reported to treat intracranial hemorrhage and ischemic stroke. [95,96] Therefore, this study mainly reviews TCM with the effects of activating blood and resolving stasis and its ingredients. [97] 4.1.…”
Section: Ciri Targets the Jak/stat Pathway To Boost Cell Proliferatio...mentioning
confidence: 99%
“…A previous systematic review and meta-analysis of 56 publications that evaluated the effect of acupuncture on rehabilitation after IS in terms of exercise rehabilitation, analgesic effects, and perfusion volume around the infarct and ischemic penumbra, indicated a positive effect of acupuncture on rehabilitation [20] . A recent systematic review indicated that acupuncture is a safe and effective treatment for IS, improving neurological function, cognition, and activities of daily living in patients [21] . A randomized single-blind clinical study of 74 patients with IS also demonstrated significant improvements in neurological function, motor function, and activities of daily living [22] .…”
Section: Introductionmentioning
confidence: 99%